The Drosophila Polycomb Group Protein Psc Contacts ph and Pc through Specific Conserved Domains - Kyba, Michael (American Society for Microbiology, 1998)
The Polycomb group proteins are transcriptional repressors that are thought to act through multimeric nuclear complexes. We show that ph and Psc coprecipitate with Pc from nuclear extracts. We have analyzed the domains required for the association of Psc with ph and Pc by using the yeast two-hybrid system and an in vitro protein-binding assay. Psc and ph interact through regions of sequence conservation with mammalian homologs, i.e., the H1 domain of ph (amino acids 1297 to 1418) and the helix-turn-helix-containing region of Psc (amino acids 336 to 473). Psc contacts Pc primarily at the helix-turn-helix-containing region of Psc (amino acids 336 to 473), but also at the ring finger (amino acids 250 to 335). The Pc chromobox is not required for this interaction. We discuss the implication of these results for the nature of the complexes formed by Polycomb group proteins.